2003
DOI: 10.1097/01.ju.0000080296.54262.c8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lipoxygenase in Human Bladder Carcinoma and Growth Inhibition by Its Inhibitors

Abstract: Lipoxygenase is induced in bladder cancer. Results suggest that lipoxygenase inhibitors may mediate potent antiproliferative effects against bladder cancer cells. Thus, lipoxygenase may become a new target in the treatment of bladder tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 18 publications
1
75
0
Order By: Relevance
“…7,[9][10][11] In the current paper, we investigated the flavonoids, baicalein and apigenin, as possible 12-hLO selective inhibitors, because, baicalein has been used in numerous citations as a selective inhibitor against 12-hLO in mammalian cells. [37][38][39][40][41][42][43] In order to investigate this detergent effect further, we included another flavonoid, apigenin, which we previously demonstrated to be a potent LO inhibitor. 16 Apigenin is a good candidate for comparison with baicalein due to its similar structure to baicalein, except for the re-positioning of one alcohol group (Figure 1).…”
Section: Insert Figure 4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[9][10][11] In the current paper, we investigated the flavonoids, baicalein and apigenin, as possible 12-hLO selective inhibitors, because, baicalein has been used in numerous citations as a selective inhibitor against 12-hLO in mammalian cells. [37][38][39][40][41][42][43] In order to investigate this detergent effect further, we included another flavonoid, apigenin, which we previously demonstrated to be a potent LO inhibitor. 16 Apigenin is a good candidate for comparison with baicalein due to its similar structure to baicalein, except for the re-positioning of one alcohol group (Figure 1).…”
Section: Insert Figure 4 Discussionmentioning
confidence: 99%
“…One specific flavonoid LO inhibitor is baicalein, a major component in the root of Scutellaria baicalensis (1.9% of total root), and has been shown to induce apoptosis in breast, prostate, colon and pancreatic cancer cell lines. [33][34][35][36] In all cases, the potency of baicalein is thought to be due to the selective inhibition of platelet 12-hLO, [37][38][39][40][41][42][43] thus interrupting only part of the arachidonic acid metabolic pathway, however, the basis of this supposition is unclear. The most cited reference, by Sekiya and Okuda, indicated only that baicalein was selective to platelet 12-hLO versus cyclooxygenase (COX), but not versus the other LO isozymes.…”
Section: Introductionmentioning
confidence: 99%
“…In a more generic approach, a number of investigations have found a correlation between mRNA expression levels of 5-and/or 12-LOX and cancer pathobiology, whereby increased LOX expression levels were noted in a broad range of cancers including breast, pancreatic, prostate, lung, urinary bladder, leukaemia and colon cancer [63,64,65,66,67,68,69]. With regards to 15-LOX, there is evidence for opposing theories on correlation of expression levels with carcinogenesis where both over-and under-expression has been observed in cancerous cells [70,71].…”
Section: Figurementioning
confidence: 99%
“…Among these, recent studies have revealed potential roles of the 5-, 12-, and 15-lipoxygenase (LO) pathways in cancer progression. For example, 5-and 12-LO are overexpressed in bladder cancer tissues and LO inhibitors inhibited growth of bladder cancer and induced apoptosis (Yoshimura et al, 2003;Hayashi et al, 2006). In accordance with the suggested role of 12-LO in cancer, 12(S)-hydroxyeicosatetraenoic acid (12(S)-HETE), a 12-LO pathway metabolite, was shown to influence tumor progression (Nie et al, 2006).…”
Section: Introductionmentioning
confidence: 81%